2019
DOI: 10.1088/1674-1056/28/6/068202
|View full text |Cite
|
Sign up to set email alerts
|

Improved electrochemical performance of Li(Ni0.6Co0.2Mn0.2)O2 at high charging cut-off voltage with Li1.4Al0.4Ti1.6(PO4)3 surface coating*

Abstract: Li(Ni0.6Co0.2Mn0.2)O2 has been surface-modified by the lithium-ion conductor Li1.4)Al0.4)Ti1.6)(PO4)3 via a facile mechanical fusion method. The annealing temperature during coating process shows a strong impact on the surface morphology and chemical composition of Li(Ni0.6Co0.2Mn0.2)O2. The 600-°C annealed material exhibits the best cyclic stability at high charging cut-off voltage of 4.5 V (versus Li … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The details of the coating layer of HC-LCO are shown in Figure 2d. It could be seen that a uniform layer with a thickness of more than 20 nm covers the surface of HC-LCO, which is different from the morphology of Bare-LCO (with a clean and smooth surface as shown in 40,41 When considering the AZO and LAGP mixture as a solid electrolyte composite, the AZO oxides additive could be believed to enhance the Li-ion conductivity as well. It is reported that Al 2 O 3 adding into LiI or Li 2 ZnI 4 can enhance the interfacial Li-ion conductivity in the nanosized system, and finally the Li-ion conductivity can obtain an improvement with 3 or 4 orders of magnitudes.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The details of the coating layer of HC-LCO are shown in Figure 2d. It could be seen that a uniform layer with a thickness of more than 20 nm covers the surface of HC-LCO, which is different from the morphology of Bare-LCO (with a clean and smooth surface as shown in 40,41 When considering the AZO and LAGP mixture as a solid electrolyte composite, the AZO oxides additive could be believed to enhance the Li-ion conductivity as well. It is reported that Al 2 O 3 adding into LiI or Li 2 ZnI 4 can enhance the interfacial Li-ion conductivity in the nanosized system, and finally the Li-ion conductivity can obtain an improvement with 3 or 4 orders of magnitudes.…”
Section: Resultsmentioning
confidence: 91%
“…The fast Fourier transformation (FFT) results of regions I and II also confirm the LAGP and AZO phases in the coating layer. During the mechanical fusion process, due to the high shear and compression forces, resulting from the high-speed rotation and pressing of the plunger chip, LAGP and AZO nanocrystals are successfully mixed and coated onto host LCO particles. , When considering the AZO and LAGP mixture as a solid electrolyte composite, the AZO oxides additive could be believed to enhance the Li-ion conductivity as well. It is reported that Al 2 O 3 adding into LiI or Li 2 ZnI 4 can enhance the interfacial Li-ion conductivity in the nanosized system, and finally the Li-ion conductivity can obtain an improvement with 3 or 4 orders of magnitudes. In addition, the electronic conductivities of HC-LCO and Bare-LCO powders were measured and the results in Figure S6 show that the electronic conductivity of LCO powders is enhanced after LAGP-AZO comodification.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The most significant difference between coating and water washing is that coating stabilizes the surface structure and makes the treated cathode have a strong resistance to H 2 O and CO 2 in the following storage process. [ 41,72 ] Besides, the production process of Ni‐rich cathode materials can be simplified because there is no washing and subsequent calcination process, which also reduces the cost and production time (Figure 6). Sung et al .…”
Section: Methods To Eliminate Residual Lithium Compoundsmentioning
confidence: 99%
“…[ 39 ] There are many literatures about the origins, influences, and modification methods of RLCs generated on Ni‐rich cathode materials’ surface. [ 40‐43 ] Therefore, we are committed to making a systematic explanation and solutions for the RLCs.…”
Section: Introductionmentioning
confidence: 99%
“…These ions tend to dissolve into the electrolyte, and this process accelerates the capacity fade of the battery. The most effective approach for protecting the LNMO particles is to avoid their direct contact with the electrolyte. This could be achieved by covering their surface with a protective layer. The coating of cathode materials with Li 1.3 Al 0.3 Ti 1.7 ­(PO 4 ) 3 (LATP) has been largely reported in the literature. Generally, it is known that the conductivity of the Li 1+ x Al x Ti 2– x ­(PO 4 ) 3 materials is related to their composition and the maximum stability for the R 3̅ c structure, and enhanced conductivity was observed for x = 0.3 …”
mentioning
confidence: 99%